2000
DOI: 10.1128/jvi.74.9.4064-4073.2000
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of an Equine Foamy Virus

Abstract: Foamy viruses (FVs) are complex retroviruses which have been isolated from different animal species including nonhuman primates, cattle, and cats. Here, we report the isolation and characterization of a new FV isolated from blood samples of horses. Similar to other FVs, the equine foamy virus (EFV) exhibits a highly characteristic ultrastructure and induces syncytium formation and subsequent cell lysis on a large number of cell lines. Molecular cloning of EFV reveals that the general organization is that of ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
80
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 29 publications
2
80
0
Order By: Relevance
“…Interestingly, the equine and bovine FV possess sequences homologous to the intracellular assembly domain (Fig. 1A) but lack the ER retention signal on the Env protein and, correspondingly, bud virus solely from the PM (21,42). Recently, it has been reported that the N terminus of the leader peptide of SFVcpz(hu) Env, termed the budding domain, is required for efficient particle release (25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the equine and bovine FV possess sequences homologous to the intracellular assembly domain (Fig. 1A) but lack the ER retention signal on the Env protein and, correspondingly, bud virus solely from the PM (21,42). Recently, it has been reported that the N terminus of the leader peptide of SFVcpz(hu) Env, termed the budding domain, is required for efficient particle release (25).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of this region of FV Gag with the CTRS of MPMV reveals a number of identical residues, comprising a domain of FV Gag [GXWGX 3 RX 7 L (Q/V)D], centered on the conserved Arg (7,42). We predicted that if cytoplasmic assembly of FV capsids is mediated by sequences in this region, mutation of conserved residues might block assembly altogether, since the FV Gag protein is not myristylated and is not known to possess a membrane-targeting signal.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although FV cause a persistent infection, they are harmless, implying that the virus may be a valuable tool for viral vector development. FV have been isolated and cloned from a variety of primate (for references see below) and non-primate hosts (Holzschu et al, 1998;Tobaly-Tapiero et al, 2000;Winkler et al, 1997). Evolutionary studies would benefit from the characterization of the FV genomic diversity, but to date, only a few primate FVs from macaques (SFVmac) (Kupiec et al, 1991), African green monkey (SFVagm) (Renne et al, 1992), orang-utan (SFVora) (Verschoor et al, 2003), chimpanzees (SFVcpz) (Herchenröder et al, 1994(Herchenröder et al, , 1995, spider monkey (SFVspm) (Thümer et al, 2007), marmoset and squirrel monkey (Pacheco et al, 2010) have been cloned and completely sequenced.…”
mentioning
confidence: 99%
“…FVs are found in primates, including humans, as well as in non-primates, including cows, cats and horses (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%